The role of parental child marriage in children's food security and nutritional status: a prospective cohort study in Indonesia - Hidayah, Isnawati; Suryahadi, Asep; Palmisano, Flaviana; Kiefte-de Jong, Jessica C. (Frontiers in Public Health, 2024)
ObjectivesAssessing children's food and nutrition security in Indonesia, especially among children from parents who experienced child marriage, is crucial for policymakers. This study investigates the role of parental child marriage in children's food security and nutritional status.MethodsWe analyze data from Indonesia Family Life Survey (IFLS) wave 4 (2007) and 5 (2014), involving 1,612 households. We employ OLS and binary logit regression analysis.ResultsOur analysis reveals that parental child marriage is associated with higher probability of children being stunted and experiencing food insecurity. Additionally, parental child marriage correlates with higher BMI-for-age z-scores, which increase the risk of obesity, and lower Food Consumption Scores (FCS).RecommendationImplementing community initiatives, economic empowerment, healthcare access, and gender-sensitive and integrated policies is crucial for enhancing food security and improving nutritional status among childen in families affected by child marriage.